Phytochemical, Metabolite Compound, and Antioxidant Activity of Clinacanthus nutans Leaf Extract from Indonesia - Nurlaili Susanti; Arifa Mustika; Junaidi Khotib; Roihatul Muti’ah; Maftuchah Rochmanti (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The antioxidant properties from medicinal plants have protective effects against oxidative stress-linked diseases. Their antioxidant capacities are related to phenolic compounds, including phenols and flavonoids. Clinacanthus nutans, a native to Asia, including Malaysia, Thailand, and Indonesia, are used for treating diabetes and other diseases, but the exploration of the plant in Indonesia is still limited. Therefore, this study aimed to reveal the phytochemical constituents, metabolic compounds, and antioxidant activity of C. nutans extracts. Dried leaf powder was extracted with 70% ethanol and aqueous, each extract was subjected to qualitative phytochemical screening. Subsequently, total phenolic and flavonoid content was calculated using Folin-Ciocalteu and AlCl3 colorimetric assay. The antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. The profiles of phenolic and flavonoid compounds of 70% ethanolic extract were investigated by LC MS/MS. Phytochemical screening showed that the extracts contain phenolic, flavonoid, tannin, and saponin. The total phenolic content of the 70% ethanol and aqueous extract was 4.14±1.9% mgGAE/g and 3.89±3.2% mgGAE/g, respectively. Meanwhile, the total flavonoid content obtained was 0.19±1.0% mgQE/g and 0.03±0.5% mgQE/g for 70% ethanol and aqueous extracts, respectively. Both extracts showed high antioxidant activity, with DPPH IC50 30.57 ????g/mL for 70% ethanol and 37.24 ????g/mL for aqueous extract. LC-MS/MS analysis of 70% ethanol extract revealed 5 phenolic and 3 flavonoid compounds, where DL-glutamic monohydrate and Boesenbergin B were the most dominant based on the percentage of area under the curve. C. nutans originating from Indonesia can be a good source of natural antioxidants because 70% ethanol and aqueous extract show high phytochemical content and antioxidant activity.